Lemongrass effects on IL-1 and IL-6 production by macrophages - Sforcin, J. M. [UNESP]; Amaral, J. T. [UNESP]; Fernandes, A. [UNESP]; Sousa, J. P. B.; Bastos, J. K. (Taylor & Francis Ltd, 2009)
Cymbopogon citratus has been widely recognised for its ethnobotanical and medicinal usefulness. Its insecticidal, antimicrobial and therapeutic properties have been reported, but little is known about its effect on the immune system. This work aimed to investigate the in vivo effect of a water extract of lemongrass on pro-inflammatory cytokine (IL-1 and IL-6) production by macrophages of BALB/c mice. The action of lemongrass essential oil on cytokine production by macrophages was also analysed in vitro. The chemical composition of the extract and the oil was also investigated. Treatment of mice with water extract of lemongrass inhibited macrophages to produce IL-1 but induced IL-6 production by these cells. Lemongrass essential oil inhibited the cytokine production in vitro. Linalool oxide and epoxy-linalool oxide were found to be the major components of lemongrass water extract, and neral and geranial were the major compounds of its essential oil. Taken together, these data suggest an anti-inflammatory action of this natural product.
Keywords: lemongrass; Cymbopogon citratus; Poaceae; essential oil; macrophages; cytokines